2021
DOI: 10.1021/acsomega.1c00658
|View full text |Cite
|
Sign up to set email alerts
|

Zn(II)-tetracarboxy-phthalocyanine-Sensitized TiO2 Thin Films as Antimicrobial Agents under Visible Irradiation: a Combined DFT and Experimental Study

Abstract: In this article, we studied the antimicrobial activity of TiO2 sensitized by the Zn­(II)-tetracarboxy-phthalocyanine (TcPcZn) complex using TiO2-Degussa P25 as a semiconductor source. The TiO2 thin films were deposited by the doctor blade method and were sensitized by the chemisorption process. The obtained compounds were characterized using Fourier transform infrared spectroscopy, UV–vis spectrophotometry, Raman spectroscopy, diffuse reflectance spectroscopy, and scanning electron microscopy. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 94 publications
1
1
0
Order By: Relevance
“…Grafting TiO 2 with peripherally-modified phthalocyanines reduced the E g of the photocatalytic material. The results are consistent with the literature [58][59][60]. There is a clear difference between the E g of bare TiO 2 and the E g of composites of peripherally-modified Pcs and TiO 2 ; however, these composites express similar E g values.…”
Section: Uv Diffuse Reflectance Spectroscopy (Drs)-band Gap Determina...supporting
confidence: 92%
“…Grafting TiO 2 with peripherally-modified phthalocyanines reduced the E g of the photocatalytic material. The results are consistent with the literature [58][59][60]. There is a clear difference between the E g of bare TiO 2 and the E g of composites of peripherally-modified Pcs and TiO 2 ; however, these composites express similar E g values.…”
Section: Uv Diffuse Reflectance Spectroscopy (Drs)-band Gap Determina...supporting
confidence: 92%
“…Metal porphyrins and phthalocyanines (Pcs) have gained high interest in the field of photocatalysis due to their photosensitizing properties in the visible and NIR range and to their high photostability. Numerous studies have demonstrated that Pcs can activate wide bandgap semiconductors like TiO2 [22,23], ZnO [24,25] or graphitic carbon nitride C3N4 [26,27]. The coupling of BiOX with porphyrins and Pcs has been the subject of far fewer studies.…”
Section: Introductionmentioning
confidence: 99%